2018
DOI: 10.1098/rsos.171928
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected solvent effects on the UV/Vis absorption spectra of o -cresol in toluene and benzene: in contrast with non-aromatic solvents

Abstract: Cresol is a prototype molecule in understanding intermolecular interactions in material and biological systems, because it offers different binding sites with various solvents and protonation states under different pH values. It is found that the UV/Vis absorption spectra of o-cresol in aromatic solvents (benzene, toluene) are characterized by a sharp peak, unlike the broad double-peaks in 11 non-aromatic solvents. Both molecular dynamics simulations and electronic structure calculations revealed the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 70 publications
0
21
0
1
Order By: Relevance
“…[24][25][26] Substantial research proved that the host solvent played a dominant role in the morphology control of the active layer, which influenced the performance of the final devices. [27][28][29] By carefully tuning the print parameters, Zhao et al reported the effects of halogenated and hydrocarbon solvents on PDBD-T-2F:BTP-4F active layer based BHJ OSC. A higher degree of crystallinity with a more minor phase separation structure was observed in ortho-xylene processed thin films, yielding the promising champion efficiency of 15.6%.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Substantial research proved that the host solvent played a dominant role in the morphology control of the active layer, which influenced the performance of the final devices. [27][28][29] By carefully tuning the print parameters, Zhao et al reported the effects of halogenated and hydrocarbon solvents on PDBD-T-2F:BTP-4F active layer based BHJ OSC. A higher degree of crystallinity with a more minor phase separation structure was observed in ortho-xylene processed thin films, yielding the promising champion efficiency of 15.6%.…”
Section: Introductionmentioning
confidence: 99%
“…Similar effects were reported also by Zheng et al . 19 As a consequence both SC2 and BC15 have no maxima below 280 nm in those solvents. The emission spectra, however, are much more dependent on the polarity because the values of the fluorescence maxima vary more significantly for both compounds.…”
Section: Resultsmentioning
confidence: 97%
“…The absorption spectrum of 1,4-anisidine was measured at pH= 6.0, while in our FPMD simulations molecules solvated in aqueous solution at neutral pH, and this difference may cause a shift in the UV-visible absorption. 70,77 The QC spectra were obtained by averaging only a few hundred frames for each molecule.…”
Section: Resultsmentioning
confidence: 99%